2020
DOI: 10.1097/hcr.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of the Pulmonary Rehabilitation Program in a Rehabilitation Center

Abstract: We reported the case of a patient referred for a respiratory rehabilitation program (RRP) after intensive care unit stay, who achieved a meaningful functional recovery after 3 wk of RRP, partially carried out in an ad hoc isolation ward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 13 publications
1
31
0
3
Order By: Relevance
“…[ 30 , 56 ] Early inpatient rehabilitation includes respiratory care, bed mobilization, bed-to- chair transfer, sit-to-stand training, assisted walking, and neuromuscular electrical stimulation in limb muscles result in improved respiratory function, quadriceps muscle function, and walking capacity measured on Barthel dyspnea index, quadriceps size, and EuroQoL questionnaire. [ 30 , 34 ] Besides, a dynamic patient-guided robotic suspension system assists in developing ambulation, ADL performance, 6MWT, and 10-meter walk test speed. [ 35 ] In COVID-19, an eight-segment traditional Chinese PR exercises regime is considered promising, particularly when prescribed with conventional breathing techniques and proprioceptive neuromuscular facilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 30 , 56 ] Early inpatient rehabilitation includes respiratory care, bed mobilization, bed-to- chair transfer, sit-to-stand training, assisted walking, and neuromuscular electrical stimulation in limb muscles result in improved respiratory function, quadriceps muscle function, and walking capacity measured on Barthel dyspnea index, quadriceps size, and EuroQoL questionnaire. [ 30 , 34 ] Besides, a dynamic patient-guided robotic suspension system assists in developing ambulation, ADL performance, 6MWT, and 10-meter walk test speed. [ 35 ] In COVID-19, an eight-segment traditional Chinese PR exercises regime is considered promising, particularly when prescribed with conventional breathing techniques and proprioceptive neuromuscular facilitation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective inception cohort, early PR of COPD patients within 90 days of hospital discharge was associated with a significantly lower death risk over one year (hazard ratio [HR], 0.63, 95% confidence interval [CI]: 0.57 to 0.69 (p <0.001). [ 34 ] Additional PR sessions were also associated with a reduced death risk (HR, 0.91, 95% CI: 0.85 to 0.98, p=0.01). [ 69 ] Besides, patients who adhere to PR techniques for a long-time, usually require less utilization of healthcare utilization than non-adherent patients.…”
Section: Discussionmentioning
confidence: 99%
“…Under these premises, a standard rehabilitation program for ARDS should include an early intervention starting during the ICU stay and continuing to the subacute phase to reduce the complications of immobilization and the effects of prolonged mechanical ventilation. However, during the COVID-19 pandemic, the majority of patients could not receive rehabilitation treatment in ICU and this task was left to specialized rehabilitation centers, which had already undergone unexpected and urgent organizational changes [ 23 ]. For example, due to the risk of spreading the infection to other patients and health professionals, we divided inpatient rehabilitation into two phases.…”
Section: Discussionmentioning
confidence: 99%
“… 89 Kensuke et al and Simone et al reported on severe COVID-19 patients treated with muscle electrical stimulation in the ICU ward. 90 , 91 Therefore, for people with more severe COVID-19 illness , WBV or electro muscle stimulation may play an important role in their physical rehabilitation.…”
Section: Exercise Methods Selectionmentioning
confidence: 99%